2021
DOI: 10.1002/cti2.1242
|View full text |Cite
|
Sign up to set email alerts
|

Influenza, but not SARS‐CoV‐2, infection induces a rapid interferon response that wanes with age and diminished tissue‐resident memory CD8+ T cells

Abstract: Older individuals exhibit a diminished ability to respond to and clear respiratory pathogens and, as such, experience a higher rate of lung infections with a higher mortality rate. It is unclear why respiratory pathogens impact older people disproportionately. Using human lung tissue from donors aged 22-68 years, we assessed how the immune cell landscape in lungs changes throughout life and investigated how these immune cells respond following in vitro exposure to influenza virus and SARS-CoV-2, two clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…A high level of cross-compensation is thus implicated, as is described in influenza infection [ 84 ]. In vitro experiments show that SARS-CoV-2 replication is sensitive to type I and III IFNs, although infection does not stimulate particularly high levels of IFN [ 85 , 103 , 104 ]. A number of SARS-CoV-2 encoded proteins inhibit IFN production and signaling [ 98 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…A high level of cross-compensation is thus implicated, as is described in influenza infection [ 84 ]. In vitro experiments show that SARS-CoV-2 replication is sensitive to type I and III IFNs, although infection does not stimulate particularly high levels of IFN [ 85 , 103 , 104 ]. A number of SARS-CoV-2 encoded proteins inhibit IFN production and signaling [ 98 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, recent evidence suggests the quality of the Trm re-call response can be influenced by the identity of the APC which triggers their reactivation, with presentation by hematopoietic APCs-regulating chemokine/cytokine production, and presentation by nonhematopoietic APCs-regulating proliferation 94 . Studies characterizing the immune cell landscape in lung tissue from human organ donors revealed that the human lung harbors a large pool of influenza-specific CD8 + Trm 51 , 93 , 95 97 . These cells were shown to be highly proliferative and polyfunctional, composed of a diverse TCRαβ repertoire, and a proportion were cross-reactive against multiple influenza strains 93 , 98 .…”
Section: The Protective Capacity Of Respiratory Tract Trmmentioning
confidence: 99%
“…This attrition is consequential as animal studies clearly show that a loss of influenza-specific Trm in the parenchyma and airways correlates with waning cross-protective immunity 17 , 116 , 117 . Similarly, influenza-specific CD8 + Trm in human lung tissue wane with advanced age, and this resulted in a lag in the development of an antiviral response following influenza exposure 95 . The attrition of lung CD8 + Trm is not restricted to influenza-specific Trm cells, as similar findings are observed following Sendai virus 116 , 118 and RSV 101 infections in mice.…”
Section: The Persistence Of Respiratory Tract Trmmentioning
confidence: 99%
“…A high level of cross-compensation is thus implicated, as is described in influenza infection (71). In vitro experiments show that SARS-CoV-2 replication is sensitive to type I and III IFNs, although infection does not stimulate particularly high levels of IFN (72, 88, 89). A number of SARS-CoV-2 encoded proteins inhibit IFN production and signaling (83, 90, 91).…”
Section: Discussionmentioning
confidence: 99%